Physical controls of Southern Ocean deep-convection variability in CMIP5 models and the Kiel Climate Model - Reintges, Annika; Martin, Torge; Latif, Mojib; Park, Wonsun (Geophysical Research Letters, 2017)
Global climate models exhibit large biases in the Southern Ocean. For example, in models Antarctic bottom water is formed mostly through open-ocean deep-convection rather than through shelf convection. Still, the timescale, region, and intensity of deep-convection variability vary widely among models. We investigate the physical controls of this variability in the Atlantic sector of the Southern Ocean, where most of the models simulate recurring deep-convection events. We analyzed output from eleven exemplary CMIP5 models and four versions of the Kiel Climate Model (KCM). Of several potential physical control parameters that we tested, the ones shared by all these models are: Stratification in the convection region influences the timescale of the deep-convection variability, i.e. models with a strong (weak) stratification vary on long (short) timescales. And, sea ice volume affects the modeled mean state in the Southern Ocean: large (small) sea ice volume is associated with a non-convective (convective) predominant regime.